Self-Control in Aiming Supports Coping With Psychological Pressure in Soccer Penalty Kicks - Navia, José A.; van der Kamp, John; Avilés, Carlos; Aceituno, Jesús (Frontiers in Psychology, 2019)
This study addressed the question whether coaches better allow athletes to self-control their decisions when under pressure or whether to impose a decision upon them. To this end, an experiment was conducted that manipulated the soccer kickers’ degree of control in decision making. Two groups of elite under-19 soccer players (n=18) took penalty kicks in a self-controlled (i.e., kickers themselves decided to which side to direct the ball) and an externally-controlled condition (i.e., the decision to which side to direct the ball was imposed upon the kickers). One group performed the penalty kick under psychological pressure (i.e., the present coaching staff assessed their performance), while the second group performed without pressure. Just before and after performing the kicks, CSAI-2 was used to measure cognitive and somatic anxiety and self-confidence. Further, the number of goals scored, ball placement and speed, and the duration of preparatory and performatory behaviors were determined. The results verified increased levels of cognitive and somatic anxiety after performing the kicks in the pressured group compared to the no pressure group. In addition, degree of self-control affected the participants’ performance, particularly in the pressured group. They scored more goals and placed the kicks higher in the self-controlled than in the externally-controlled condition. Participants also took more time preparing and performing the run-up in the self-controlled condition. Findings indicate that increased self-control helps coping with the debilitating effects of pressure and can counter performance deteriorations. The findings are discussed within the framework of self-control theories, and recommendations for practitioners and athletes are made.